Importance of Financial Technologies and Digitalization of Banks in the Field of Banking Services (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article discusses the use of financial technologies in the commercial banking sector of Uzbekistan. Ways, problems and prospects of digitalization of commercial banks ' services are highlighted. Also, the scientific-theoretical basis of providing both modern and remote banking services in commercial banks and the economic importance of digital banks were studied, suggestions and recommendations were formulated on the involvement of financial technologies by commercial banks in the context of the digitization of the banking system.Also, the essence, characteristics, principles of the digital economy, the experiences of developed countries in the field of commercial banking and the possibilities of the emergence of digital banks in our republic were studied.